Therapeutic Targeting Hypoxia-Inducible Factor (HIF-1) in Cancer: Cutting Gordian Knot of Cancer Cell Metabolism - Sharma, Abhilasha; Sinha, Sonam; Shrivastava, Neeta (Frontiers in Genetics, 2022)
Metabolic alterations are one of the hallmarks of cancer, which has recently gained great attention. Increased glucose absorption and lactate secretion in cancer cells are characterized by the Warburg effect, which is caused by the metabolic changes in the tumor tissue. Cancer cells switch from oxidative phosphorylation (OXPHOS) to aerobic glycolysis due to changes in glucose degradation mechanisms, a process known as “metabolic reprogramming”. As a result, proteins involved in mediating the altered metabolic pathways identified in cancer cells pose novel therapeutic targets. Hypoxic tumor microenvironment (HTM) is anticipated to trigger and promote metabolic alterations, oncogene activation, epithelial-mesenchymal transition, and drug resistance, all of which are hallmarks of aggressive cancer behaviour. Angiogenesis, erythropoiesis, glycolysis regulation, glucose transport, acidosis regulators have all been orchestrated through the activation and stability of a transcription factor termed hypoxia-inducible factor-1 (HIF-1), hence altering crucial Warburg effect activities. Therefore, targeting HIF-1 as a cancer therapy seems like an extremely rational approach as it is directly involved in the shift of cancer tissue. In this mini-review, we present a brief overview of the function of HIF-1 in hypoxic glycolysis with a particular focus on novel therapeutic strategies currently available.